Chromosome Painting Using Chromosome-Specific BAC Clones - Mandáková, Terezie M; Lysak, Martin A (Methods in molecular biology (Clifton, N.J.), 2023)
Chromosome painting (CP) refers to visualization of large chromosome regions, chromosome arms or entire chromosomes via fluorescence in situ hybridization (FISH) of chromosome-specific DNA sequences. For CP in crucifers (Brassicaceae), typically contigs of chromosome-specific bacterial artificial chromosomes (BAC) from Arabidopsis thaliana are applied as painting probes on chromosomes of A. thaliana or other species (comparative chromosome painting, CCP). CP/CCP enables to identify and trace particular chromosome regions and/or chromosomes throughout all mitotic and meiotic stages as well as corresponding interphase chromosome territories. However, extended pachytene chromosomes provide the highest resolution of CP/CCP. Fine-scale chromosome structure, structural chromosome rearrangements (such as inversions, translocations, centromere repositioning), and chromosome breakpoints can be investigated by CP/CCP. BAC DNA probes can be accompanied by other types of DNA probes, such as repetitive DNA, genomic DNA, or synthetic oligonucleotide probes. Here, we describe a robust step-by-step protocol of CP and CCP which proved to be efficient across the family Brassicaceae, but which is also applicable to other angiosperm families.
Keywords: BAC FISH; DNA sondy; buněčné klony; DNA; malování chromozomů; Chromosome Painting; umělé bakteriální chromozomy; Nick translation; Chromosomes; Brassicaceae; Chromosomes, Artificial, Bacterial; Arabidopsis thaliana; Fluorescence in situ hybridization (FISH); Chromosome painting; hybridizace in situ fluorescenční; Arabidopsis; Clone Cells; DNA Probes; In Situ Hybridization, Fluorescence; chromozomy